Self-Care Management of Type II Diabetes Mellitus Patients at Siti Fatimah Az-Zahra Hospital, South Sumatra Province - Joko Tri Wahyudi (IKesT Muhammadiyah Palembang, 2024)
Background: Diabetes mellitus is an endocrine and metabolic disease that involves failure to use or produce insulin. Disease in DM occurs due to high levels of glucose in the blood that exceed normal limits. In type II DM sufferers, it is necessary to monitor and understand lifestyle behavior in self-care management, which consists of adjusting diet, physical exercise, foot care, medication, and glucose control. Self-care management (Self Care) is an individual's ability to manage self-care. The goal of self-care management is to prevent the complications of Diabetes Mellitus. Research Objectives: To find out how self-care management is in type II DM patients. Methods: This research method uses a descriptive analytic method with a total of 88 respondents. Results: The average age of the respondents was 49 years old, female (60.2%), and last education was SMA/SMK (47.7%). Occupation of housewives (46.6%), dietary compliance of DM patients is low (56.8%), moderate physical activity (44.3%), foot care compliance (55.7%), glucose control (50%), taking moderate medication (55.7%). Conclusion: The level of adherence to the diet of patients with low diabetes was 50 patients (56.8%) and high was 38 patients (43.2%), Physical activity patients with moderate diabeere 39 patients (44.3%), severe were 29 patients (33, 0%), and mild in 20 patients (22.7%), adherence to foot care in patients with adherence to 49 patients (55.7%), and non-adherence of 39 patients (44.3%), glucose control in patients with regular diabetes ( 50.0%) and irregular 44 patients (50.0%), adherence to taking medication and moderate DM as many as 49 patients (55.7%), low as many as 20 patients (22.7%) and high as many as 19 patients (21, 6%). DM patients are expected to improve self-care management behavior to improve health status and prevent further complications.